2007
DOI: 10.1021/jo061959t
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive π-Conjugated Alkynylpyrene Oligomers:  Their Synthesis and Photophysical Properties

Abstract: We newly prepared para- and meta-linked alkynylpyrene oligomers and examined their photophysical properties. Oligomerization of monomeric building blocks was performed by CuI-promoted oxidative coupling reaction. The resulting oligomers mainly consist of 2-mer to 6-mer that were assigned on the basis of MALDI-TOF mass spectra, and the 2-mer, 3-mer, and 4-mer were isolated and fully characterized. From their absorption and fluorescence spectra, the para-linked oligomers were found to be somewhat pi-conjugated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…89 This fact inspired the same authors in the preparation of para-and meta-linked alkynylpyrene oligomers 159 and 160, and they examined their photophysical properties for possible application in optical devices ( Figure 87). 243 In this case, the preparation of the oligomers was achieved via Sonogashira coupling from a well-defined 1,6-disubstituted pyrene monomer, which allows the control of the oligomeric structure.…”
Section: Dendritic Structuresmentioning
confidence: 99%
“…89 This fact inspired the same authors in the preparation of para-and meta-linked alkynylpyrene oligomers 159 and 160, and they examined their photophysical properties for possible application in optical devices ( Figure 87). 243 In this case, the preparation of the oligomers was achieved via Sonogashira coupling from a well-defined 1,6-disubstituted pyrene monomer, which allows the control of the oligomeric structure.…”
Section: Dendritic Structuresmentioning
confidence: 99%
“…[16][17][18][19][20] Recently, alkynylpyrenes have been developed as improved pyrene-based biomolecular probes with high fluorescence quantum yields and reduced quenching of the fluorescence. [21][22][23] Recently, it was reported that the alternating copolymerization of N-alkylmaleimides (RMI) with isobutene (IB) produced high-molecular-weight copolymers [poly(RMIalt-IB)s] with excellent thermal stabilities, as well as excellent mechanical and optical properties. [24][25][26][27][28][29][30] For example, the onset temperature of the thermal decomposition was over 350 8C and the glass transition temperature (T g ) was 152 8C for poly(RMI-alt-IB) with an N-methyl substituent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, pyrene-cored crystalline oligopyrene nanowires (57, Figure 11) exhibiting multi-colored emission have been reported by Shi et al (Qu  Shi, 2004). Inoue and co-workers reported the synthesis and photophysical properties of two types of acetylene-linked -conjugated oligomers based on alkynylpyrene skeletons (Shimizu et al, 2007). The chemical structures of these alkynylpyrene oligomers 58 and 59 are also show in Figure 11, and the structural difference between 58 and 59 is only the linkage position of terminal acetylene groups on the benzene rings, i.e., para for 58 and meta for 59.…”
Section: Functionalized Pyrene-based Light-emitting Oligomers and Polmentioning
confidence: 92%